Corporate Social Responsibility (Csr) And It’s Relationship To Construction Firms - Ismail, Nazirah (Universiti Sains Malaysia, 2005)
This research attempts to analyse what is actually Corporate Social Responsibility (CSR), its relationship to construction firms and why company should take on the task of CSR. This research tried to identify what challenges and barriers they face when assuming a CSR role. Besides that, this research also tried to identify whether there is any company had already applied some parts of CSR in their management and to observe whether the CSR can improve a company reputation and goodwill.